Cyclopina oblivia sp. n. (Crustacea, Copepoda) из интерстициали Черного моря - Монченко, В.И. (Вестник зоологии, 1981)
An illustrated descriptionis givenfor Cyclopina oblivia sp. n. from the sea shore from Simeis (the Crimea) to Pitzunda (the Caucasus). It differs from the related species C. mediterranea in lengthened furca (index2 instead of 1.5), another relation of the innermost bristle to outermost one . instead o < and to furcal length less than instead of more than 3), in 2 bristles (instead of 3) on basopod of maxilliped, in equal (in length) spines of Ps. The zoogeographical relations of the new species are discussed.